Pharmacist Segments Identified from 2009, 2014, and 2019 National Pharmacist Workforce Surveys: Implications for Pharmacy Organizations and Personnel - Schommer, Jon (Pharmacy (Basel), 2020)
Background/Objective: Findings from the 2009 and 2014 National Pharmacist Workforce Surveys showed that approximately 40% of U.S. pharmacists devoted their time primarily to medication providing, 40% contributed a significant portion of their time to patient care service provision, and the remaining 20% contributed most of their time to other health-system improvement activities. The objective of this study was to characterize the U.S. pharmacist workforce into segments based on the proportion of time they spend in medication providing and patient care services and compare changes in these segments between 2009, 2014, and 2019. Methods: Data from 2009, 2014, and 2019 National Pharmacist Workforce Surveys were analyzed. Responses from 1200 pharmacists in 2009, 1382 in 2014, and 4766 in 2019 were used for analysis. Respondents working in the pharmacy or pharmacy-related fields reported both their percent time devoted to medication providing and to patient care services. Medication providing included preparing, distributing, and administering medication products, including associated professional services. Patient care services were professional services designed for assessing and evaluating medication-related needs, monitoring and adjusting patient’s treatments, and other services designed for patient care. For each year of data, pharmacist segments were identified using a two-step cluster analysis. Descriptive statistics were used for describing the characteristics of the segments. Results: For each year, five segments of pharmacists were identified. The proportions of pharmacists in each segment for the three surveys (2009, 2014, 2019) were: (1) medication providers (41%, 40%, 34%), (2) medication providers who also provide patient care (25%, 22%, 25%), (3) other activity pharmacists (16%, 18%, 14%), (4) patient care providers who also provide medication (12%, 13%, 15%), and (5) patient care providers (6%, 7%, 12%). In 2019, other activity pharmacists worked over 45 hours per week, on average, with 12 of these hours worked remotely. Patient care providers worked 41 hours per week, on average, with six of these hours worked remotely. Medication providers worked less than 40 hours per week, on average, with just one of these hours worked remotely. Regarding the number of patients with whom a respondent interacted on a typical day, medication providers reported 18 per day, patient care providers reported 11 per day, and other activity pharmacists reported 6 per day. In 2009, 8% of patient care providers worked in a setting that was not licensed as a pharmacy. In 2019, this grew to 17%. Implications/Conclusions: The 2019 findings showed that 34% of U.S. pharmacists devoted their time primarily to medication providing (compared to 40% in 2009 and 2014), 52% contributed a significant portion of their time to patient care service provision (compared to 40% in 2009 and 2014), and the remaining 14% contributed most of their time to other health-system improvement activities. Distinguishing characteristics of the segments suggested that recent growth in the pharmacist workforce has been in the patient care services, with more being provided through remote means in organizations that are not licensed as pharmacies. The findings have implications for pharmacist training, continuing education, labor monitoring, regulations, work systems, and process designs. These changes will create new roles and tasks for pharmacy organizations and personnel that will be needed to support emerging patient care services provided by pharmacists.